Nicotine preference and affective behavior of Cd81 knockout mice. - Murphy, R. Logan; Locklear, Laura L.; Niaz, M. Haris; Walton, Rebecca L.; Hudson, Alexandra D.; Fryxell, Karl J. (Psychopharmacology, 2021)
Rationale: Cd81 -/- (knockout) mice have previously been reported to have reduced cocaine preference and increased striatal dopamine content and dopamine turnover, but normal learning and memory in the Morris water maze. The effects of Cd81 on other behaviors and drugs of abuse have not been investigated. Objectives and methods: We measured the effects of Cd81 -/- in a modified two-bottle choice test for nicotine, as well as in somatic signs of nicotine withdrawal, four tests of affective behavior, and tyrosine hydroxylase gene expression assays. Results: We found that Cd81 loss-of-function significantly increased voluntary nicotine consumption and somatic signs of nicotine withdrawal. Nicotine consumption of Cd81 -/- female mice increased for 3 weeks and then remained relatively stable for the next 5 weeks, suggesting that their nicotine consumption continued to be limited by aversion to higher nicotine doses. Cd81 -/- also produced a dramatic and significant increase in struggling in the forced swim test and a significant increase in the time spent in the light chamber of the light/dark box. The elevated plus maze and the tail suspension test did not show a main effect of genotype. Therefore, we conclude that Cd81 did not have an overall effect on anxiety- or depression-like behavior. Tyrosine hydroxylase mRNA levels were unchanged. Conclusions: Cd81 knockouts have a strongly increased nicotine preference, plus a proactive response to specific stressful situations. Together with reports of increased striatal dopamine content and anecdotal reports of increased aggressiveness, these provide intriguing parallels to some aspects of post-traumatic stress disorder.